Three‐year follow‐up of implementation of evidence‐based transfusion practice in a tertiary hospital. Issue 3 (20th February 2017) - Norgaard, A.; Stensballe, J.; de Lichtenberg, T. H.; White, J. O.; Perner, A.; Wanscher, M.; Hillingsø, J.; Holm, M. L.; Mau‐Sørensen, M.; Sillesen, H.; Kjeldsen, L.; Bäck, C.; et al.
Abstract : Background and Objectives: Traditionally, Denmark has had a high rate of allogeneic red blood cell transfusion caused by a liberal transfusion practice despite the existence of restrictive guidelines. We established a Patient Blood Management programme in a tertiary hospital and report the results of the implementation of evidence‐based transfusion practice. Materials and Methods: Red blood cell transfusion quality indicators were compared with the evidence‐based guideline at hospital and department level. Based on this evaluation, wards were selected for interventions targeting doctors and nurses. The implementation process was monitored by transfusion quality and utilization data over a 3‐year period with totally 166 341 admissions in 98 960 mixed, adult medical and surgical patients. Results: At the hospital level, transfusion above the upper guideline limit decreased from 23 to 10% ( P < 0·001), and transfusion at or below the restrictive haemoglobin trigger of 7·3 g/dl increased from 7 to 19% ( P < 0·001). The percentage of single‐unit transfusions increased from 72 to 78% ( P < 0·001), and the majority of transfusion rates and volumes decreased significantly. Red cell use decreased with 41% in surgical procedures and 28% in admissions ( P < 0·001). Conclusion: The intervention was associated with a significant and sustained overall increase in compliance with national guidelines for red blood cell transfusion for non‐bleeding patients, and led to significantly fewer patients being exposed to transfusion.